The Impact Of Webrooming On Search Process Satisfaction: The Mediating Role Of User Generated Content On Skincare Product Users In Pontianak City - Charisa Tamariska Yiswi; Windi Pratiwi; Adi Mursalin (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Nowadays, many people are switching from conventional shopping to digital shopping. Even so, online shopping is considered unsafe for the public. Many consumers search for information on the internet before shopping in physical stores. The purpose of this study is to investigate how webrooming influences search process satisfaction and determine the influence of webrooming on user generated content and search process satisfaction among skincare product users. This research is quantitative research. The population in this research is all consumers using skincare products in Pontianak City who experience webrooming in the shopping process. In this study, the number of samples used was 137 respondents using purposive sampling as a sampling technique. Sampling location in Pontianak City. The results obtained from this research found that webrooming had a significant and positive influence on search process satisfaction, then user generated content had a significant and positive influence on search process satisfaction, then user generated content also had a significant and positive influence in mediating the influence of webrooming on search process satisfaction.